(untitled) (International Journal of Engineering and Computer Science, 2017)
Wireless Sensor Networks consists of large number of sensor nodes meant to collect relevant information about sensing the network. It gains low cost and low power to send a data. In WSN, there are various attacks happening against security threats. Upon this, ‘Wormhole Attack’ is the fatal attack to abolish the network performance in the network layer. Wormhole attack creates a tunnel inside the network or between networks and thereby records packets from one end and replays to other end of the network. Upon many passive attacks, Wormhole Attack is problematic to detect in the network. And in WSN, power consumption plays a vital role. The existing algorithms use probe messages and nonce information to check the validity of the node that consumes lot of energy for detection of wormhole attack. In this paper, a simple novel technique is proposed to detect the malicious wormhole node. The proposed methodology, to detect a wormhole considers the sudden change in traffic in each node as the metric. This is accomplished by setting counter values in sensor nodes.In this paper, wormhole attack is noticed by improving power consumption for each and every sensor node and it is well proven that power disbursed is less than other existing approaches. Main advantage is easy to find wormhole using simple methodology and external hardware is not necessary.